Effective Parameters, Equilibrium, and Kinetics of Fluoride Adsorption on Prosopis cineraria and Syzygium cumini Leaves. (11th January 2019) - Keshtkar, Mozhgan; Dobaradaran, Sina; Keshmiri, Saeed; Ramavandi, Bahman; Arfaeinia, Hossein; Ghaedi, Hossein
Abstract : This study was designed to present a facile and effective biosorbent from Prosopis cineraria and Syzygium cumini leave (PCL and SCL) for fluoride removal. The test was done in batch mode and the effect of contact time (5, 25, 60, 90, and 120 min), initial fluoride concentration level (3, 5, 8, and 12 mg/L), and biosorbent dose (1, 3, 5, 10, and 25 g/L) on the biosorption process were examined. The optimum conditions for the maximum fluoride removal were occurred at 1 g/L biosorbent dose and contact time of 120 (for PCL) and 90 min (for SCL). The results suggested that the pseudo‐second‐order and Langmuir isotherm models described the experimental data well. According to the Langmuir model, the maximum adsorption capacity of fluoride for PCL and SCL was attained 11.52 and 7.4 mg/g, respectively. Based on Boyd and intra‐diffusion models, the biosorption of fluoride onto PCL and SCL was mainly controlled by film‐diffusion. The study revealed the potential use of PCL and SCL as two new effective biosorbents for the removal of fluoride from aqueous solution. © 2019 American Institute of Chemical Engineers Environ Prog, 38: S429–S440, 2019